"Dialdehyde Cellulose" Nanofibers by Electrospinning as Polyvinyl Alcohol Blends: Manufacture and Product Characterization. (4th March 2018) - Hell, Slavica; Ohkawa, Kousaku; Amer, Hassan; Potthast, Antje; Rosenau, Thomas
Abstract : A nanofiber was obtained by electrospinning of "dialdehyde cellulose" (periodate-oxidized cellulose, DAC) and polyvinyl alcohol (PVA), using only water as the solvent. Celluloses of four different origins were fully oxidized with sodium periodate to water-soluble DAC. Aqueous solution of DAC showed inadequate spinnability regardless of the polymer concentration and the electrospinning conditions used. Addition of PVA improved the solution's viscoelasticity and, consequently, the solution's spinnability. We examined the effects of DAC/PVA composition and electrospinning parameters on fiber morphology. Highly homogeneous nanofibers were prepared from 1:1 up to 2:1 (weight) DAC/PVA blends while samples of lower viscosity or higher relative DAC contents resulted in continuous, beaded fiber networks. Characterization of the electrospun fabrics revealed a highly crosslinked DAC structure reinforced with PVA, strongly interacting through hemiacetal bonds and hydrogen bonding. Fluorescence labeling confirmed the presence of reactive aldehyde functionalities in the electrospun web. The versatile properties of DAC as reactive material can now be imparted on electrospun fiber and nanofiber material – which was not possible so far –further widening the application scope of this interesting cellulose derivative.